2018
DOI: 10.1111/rda.13336
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear competence and genetic expression of growth differentiation factor‐9 (GDF‐9) of canine oocytes in 3D culture

Abstract: To evaluate the ability of a 3D culture system in improving the nuclear and molecular competence of canine oocytes, barium alginate microcapsules were used for in vitro maturation (IVM) and the expression profile of one selected oocyte‐secreted factor, the growth differentiation factor‐9 (GDF‐9) was analysed. In Experiment I, canine grade I cumulus–oocyte complexes (COCs) were in vitro matured in 3D microcapsules in a controlled atmosphere for 72 hr, and meiosis resumption rates were compared to those of oocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In addition, our data showed unvaried expression of the OOEP transcript variants, OOEP1 and OOEP2. Our data on effects of 3D IVM on gene expression are in agreement with those by Morselli et al [34] who reported down-regulation of the growth differentiation factor-9 (GDF-9), another gene involved in oocyte developmental competence, in canine oocytes after 3D IVM.…”
Section: Plos Onesupporting
confidence: 92%
See 4 more Smart Citations
“…In addition, our data showed unvaried expression of the OOEP transcript variants, OOEP1 and OOEP2. Our data on effects of 3D IVM on gene expression are in agreement with those by Morselli et al [34] who reported down-regulation of the growth differentiation factor-9 (GDF-9), another gene involved in oocyte developmental competence, in canine oocytes after 3D IVM.…”
Section: Plos Onesupporting
confidence: 92%
“…Dorati et al [ 15 ] described alginate microbead preparation by the diffusion setting gelation technique in which, using a mouth-controlled hand-pulled glass Pasteur micro-pipette, single COCs were transferred into the alginate solution in culture medium and dropped into single wells of a 96-well plate containing the cross-linking agent. Morselli et al [ 32 ] developed a two-step technique in which barium alginate microcapsules were produced and subsequently injected feline and canine COCs into the inner core of the microcapsules [ 32 34 , 36 ]. Faustini et al [ 35 ] described a protocol for bioencapsulation of COCs and granulosa cells in which a suspension of granulosa cells in cross-linking solution was dropped in an alginate solution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations